Banana bacterial wilt resource - International Network for the Improvement of Banana and Plantain (2006)
Caused by the bacterium Xanthomonas campestris pv. musacearum and previously known only in Ethiopia, where it affects bananas and its close relative Ensete, Banana Xanthomonas Wilt (BXW) is spreading through East Africa. Unlike most other diseases, which mainly reduce yield, it makes the fruit unpalatable and as such threatens food security.This well-illustrated CD-Rom includes the most recent information about the disease, printable handouts and factsheets on how to recognize it and how to stop its spread, reports, selected literature and pictures and a searchable database.